Growth Hormone Menurunkan Ekspresi Protein p53 dan p21 Sel Endotel Tikus Jantan (GROWTH HORMONE REDUCES P53 AND P21 ENDOTHELIAL PROTEIN EXPRESSION IN MALE RATS) - Ratnayanti, I Gusti Ayu Dewi; Sriwidyani, Ni Putu; Primayanti, I Dewa Ayu Inten; Kamasan, I Gusti; Arijana, Nyoman; Wiryawan, I Gusti Nyoman Sri; Wahyuniari, Ida Ayu Ika; Sugiritama, I Wayan; Mayun, I Gusti Ngurah (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
The use of growth hormone (GH) treatment in aging related condition such as atherosclerosis is stillcontroversial. Previous study showed GH reduce atherosclerotic plaque and prevent endothelial cellsenescence. This study was aimed to understand the mechanism of GH effect to endothelial senescencethrough p53/p21 pathway. A randomized posttest only control group design study was conducted. Twentymale Wistar rats were randomized into five groups; negative control (P0), positive control (P1), and GHtreated group (P2, P3, P4). Negative control group was fed with standard diet, and others were fed withatherogenic diet for 20 weeks. After 10 weeks, subjects were injected subcutaneously (0,1 mL) with aquadest(P0 and P1) and increasing dose of GH (0,02 IU, 0,04 IU, and 0,08 IU) for P2, P3, P4 once a day respectivelyfor 10 weeks. In the end of the study all subjects were examined for p53 and p21 endothelial proteinexpressions. Immunohistochemistry of endothelial p53 showed reduce expression in treated groups (P0:7.28 ± 0.36; P1: 39.51 ± 1.18; P2: 32.70 ± 1.10; P3: 16.98 ± 0.78; and P4: 14.29 ± 0.38). The reduction was also observed in p21 expression (P0: 5.38 ± 0.49; P1: 37.81 ± 0.76; P2: 26.02 ± 1.54; P3: 16.37 ± 1.24; andP4: 4.82 ± 0.61. One way analysis of variance and post hoc test (LSD) analysis showed significant differencesbetween all groups (p<0.05). In conclusion, GH reduces endothelial expression of p53 and p21 and thispathway may contribute to GH effect on atherosclerotic plaque and endothelial senescence.
Keywords: growth hormone; p53; p21; endothelial cell senescence; atherosclerosis